Frontotemporal dementia subtypes based on behavioral inhibition deficits. Issue 1 (6th April 2021) - Godefroy, Valérie; Tanguy, Delphine; Bouzigues, Arabella; Sezer, Idil; Ferrand‐Verdejo, Johan; Azuar, Carole; Bendetowicz, David; Carle, Guilhem; Rametti‐Lacroux, Armelle; Bombois, Stéphanie; Cognat, Emmanuel; Jannin, Pierre; et al.
Abstract: Introduction: We aimed to investigate phenotypic heterogeneity in the behavioral variant of frontotemporal dementia (bvFTD) through assessment of inhibition deficits. Methods: We assessed occurrences of 16 behavioral inhibition deficits from video recordings of 15 bvFTD patients (early stage) and 15 healthy controls (HC) in an ecological setting. We extracted dimensions of inhibition deficit and analyzed their correlations with cognitive and clinical measures. Using these dimensions, we isolated patient clusters whose atrophy patterns were explored. Results: After identifying two patterns of inhibition deficit (compulsive automatic behaviors and socially unconventional behaviors), we isolated three behavioral clusters with distinct atrophy patterns. BvFTD‐G0 (N = 3), an outlier group, showed severe behavioral disturbances and more severe ventromedial prefrontal cortex/orbitofrontal cortex atrophy. Compared to bvFTD‐G1 (N = 6), bvFTD‐G2 (N = 6) presented higher anxiety and depression along with less diffuse atrophy especially in midline regions. Discussion: Identifying clinico‐anatomical profiles through behavior observation could help to stratify bvFTD patients for adapted treatments.